(untitled) (American Journal of Pedagogical and Educational Research, 2026)
This article examines the challenges of achieving pragmatic equivalence in literary translation, focusing specifically on the translation of “realia” - words and expressions denoting culture-specific items, customs, and concepts. Since language is deeply intertwined with culture, transferring foreign cultural markers into a target text involves more than linguistic substitution; it requires cognitive and pragmatic adaptation. Through a systematic analysis of translation methodologies, this study evaluates the effectiveness of primary strategies such as foreignization and domestication. The findings indicate that while domestication enhances readability, foreignization preserves the cultural identity of the source text, suggesting that an integrated, context-dependent approach is essential for high-quality literary translation.